The Effect of Long – Irradiation of LED Lights on The Growth and Quality of Mustard Pakchoi Plants on Hydroponic Methods of Wick Systems - Achmad Zainudin; M Abror (Procedia of Engineering and Life Science, 2021)
This study aims to determine the effect of long-irradiation of LED lights on the growth and quality of mustard pakchoi plants on hydroponic methods of wick systems. The research was conducted for 2 months from June to July 2020 in Pekukuhan Village. Mojosari Regency. Mojokerto and Plant Physiology Laboratory, University of Muhammadiyah Sidoarjo. This study used a randomized block design and arranged in one factor, namely the length of exposure and the repetition of 5 times in order to obtain 25 experimental treatment units. The results showed that there was a significant effect of the leaf area variable on the LED lighting treatment at the age of 28 and 35 days with the highest average area (45cm) at 12 hours of exposure time, while the wet weight variable showed a significant effect on the 8 hours irradiation time (96.47 gr). Testing the chlorophyll content of mustard leaves produced the highest average total chlorophyll value (29.50 mg / l) and good antioxidant activity occurred in the treatment without LED lighting with the lowest value (357,836 µg/ml) because the lower of IC50 value, the better of antioxidants activity.